Chronic Central Nervous System Expression of HIV‐1 Tat Leads to Accelerated Rarefaction of Neocortical Capillaries and Loss of Red Blood Cell Velocity Heterogeneity. (October 2014) - Silva, Jharon N.; Polesskaya, Oksana; Wei, Helen S.; Rasheed, Izad‐Yar D.; Chamberlain, Jeffrey M.; Nishimura, Christopher; Feng, Changyong; Dewhurst, Stephen
Abstract Objectives HIV‐1 infection of the CNS is associated with impairment of CBF and neurocognitive function, and accelerated signs of aging. As normal aging is associated with rarefaction of the cerebral vasculature, we set out to examine chronic viral effects on the cerebral vasculature. Methods DOX‐inducible HIV‐1 Tat‐tg and WT control mice were used. Animals were treated with DOX for three weeks or five to seven months. Cerebral vessel density and capillary segment length were determined from quantitative image analyses of sectioned cortical tissue. In addition, movement of red blood cells in individual capillaries was imaged in vivo using multiphoton microscopy, to determine RBCV and flux. Results Mean RBCV was not different between Tat‐tg mice and age‐matched WT controls. However, cortical capillaries from Tat‐tg mice showed a significant loss of RBCV heterogeneity and increased RBCF that was attributed to a marked decrease in total cortical capillary length (35–40%) compared to WT mice. Conclusions Cerebrovascular rarefaction is accelerated in HIV‐1 Tat‐transgenic mice, and this is associated with alterations in red cell blood velocity. These changes may have relevance to the pathogenesis of HIV‐associated neurocognitive disorders in an aging HIV‐positive population.